Dinuclear Re(I) Complexes as New Electrocatalytic Systems for CO2 Reduction. Issue 11 (1st June 2021) - Quartapelle Procopio, Elsa; Boni, Alessandro; Veronese, Lorenzo; Marcaccio, Massimo; Mercandelli, Pierluigi; Valenti, Giovanni; Panigati, Monica; Paolucci, Francesco
Abstract: A family of dinuclear tricarbonyl rhenium (I) complexes containing bridging 1, 2‐diazine ligand and halide anions as ancillary ligands and able to catalyze CO2 reduction is presented. Electrochemical studies show that the highest catalytic efficiency is obtained for the complex containing the 4, 5‐bipenthyl‐pyridazine and iodide as ancillary halogen ligands. This complex gives rise to TOF=15 s −1 that clearly outperforms the values reported for the benchmark mononuclear Re(CO)3 Cl(bpy) (11.1 s −1 ). The role of the substituents on the pyridazine ligand and the nature of the bridging halide ligands on the catalytic activity have been deeply investigated through a systematic study on the structure‐properties relationship to understand the improved catalytic efficiencies of this class of complexes. Abstract : Molecular electrochemistry : A new family of dinuclear tricarbonyl rhenium (I) complexes containing bridging 1, 2‐diazine ligand and halide anions (I, Cl and Br) as ancillary ligands and capable of catalyzing the CO2 reduction reaction is presented. The authors elucidate the role of the substituents on the pyridazine ligand and the nature of the bridging halide ligands on the catalytic activity through a systematic study of the structure‐properties relationship.